Virtual cardiac rehabilitation during the COVID-19 pandemic: a tertiary site experience. (11th May 2022) - Moulson, N; Robinson, J; Chan, S; Cuff, D; Ignaszewski, A; Isserow, S; Lau, B; Ordano, N; Sung, L; Werry, J; Taylor, C
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): University of British Columbia Clinician Investigator Program Background: The COVID-19 pandemic resulted in the abrupt suspension of centre-based cardiac rehabilitation (CR). Multidisciplinary virtual CR (VCR) with the use of digital, telephone, and video communication was implemented for continued care access. Exercise therapy was delivered through synchronous video-supervised sessions, pre-recorded sessions, and self-directed physical activity. Purpose: To describe patient characteristics, completion rates, and safety outcomes in a real-world VCR population. Methods: Prospective observational study of a tertiary academic CR program. VCR was implemented at pandemic onset (March 2020). Patients who were enrolled in, and either completed or dropped out, during the study period were included. Completers were defined as completing 6 months of virtual enrolment and an exit assessment. Risk was defined by the AACPVR 2020 risk categorization. Adverse cardiovascular events were defined as a patient-initiated event requiring medical assessment and stratified as exercise or non-exercise related. Continuous variables are presented as means and SD or medians and IQR. Student's t-test was used for between group comparisons. Categorical variables are presented as n (%) and compared using the χ2 test or Fischer's exact test. A p-value <0.05 was considered significant. Results: Between March 13th, 2020, and August 31st, 2021, 222 [mean age 61.8 years (SD, 12.6) 77% male], were enrolled and discharged from the VCR program (Table 1). There were 160 completers and 62 non-completers (completion rate 72%). Among the non-completers 26 attended the MD intake assessment only. The remaining 36 completed a median of 85 days (IQR 25-197). This cohort included 21 (9%) high-risk and 35 (16%) moderate risk patients. Those at moderate risk were more likely to be non-completers and those at low risk were more likely to be completers (Table 1). Two exercise and 17 non-exercise adverse events were observed (median clinical surveillance 217 days [IQR 205-240]) (Table 2). Exercise related adverse events included neurally mediated syncope during a synchronous video exercise session in a low risk patient. This was responded to as per centre developed virtual safety protocols. A second syncope related to heart block occurred in a moderate risk patient during independent physical activity and required permanent pacemaker insertion. Both patients completed the program. Three non-exercise adverse cardiac events resulted in cessation of participation included one death and two heart failure hospitalizations (Table 2). One stroke and 13 emergency department visits for cardiac symptoms occurred in completers. Conclusion: Real world VCR is feasible, including in those at moderate to high risk. Modest completion rates and a low exercise related adverse event rate were observed. Synchronous video exercise sessions with video monitoring and safety protocols may improve response to adverse exercise related events.